2013
DOI: 10.1037/a0032451
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an internet-based contingency management intervention for smoking cessation: Views of smokers, nonsmokers, and healthcare professionals.

Abstract: The acceptability of an Internet-based contingency management (CM) intervention for cigarette-smoking was evaluated in two experiments. In Experiment 1, 67 participants completed an Internet-based CM intervention and then answered questions about the intervention. Experiment 2 assessed the acceptability of the intervention among potential treatment users (smokers, n = 164), non-smokers (n = 166), and healthcare providers (n = 139), who had never used the intervention. Participants in Experiment 2 were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
(77 reference statements)
9
33
0
Order By: Relevance
“…Other studies that have used noncontingent comparison groups did not include most of these factors (e.g., Higgins, Wong, Badger, Ogden, & Dantona, 2000; Silverman et al, 1998), particularly the frequent monitoring, immediate feedback, and quantitative and graphed goals. Participants in this study also indicated that they found these features to be some of the most helpful in promoting abstinence (reported in Raiff et al, 2013). …”
Section: Discussionmentioning
confidence: 63%
“…Other studies that have used noncontingent comparison groups did not include most of these factors (e.g., Higgins, Wong, Badger, Ogden, & Dantona, 2000; Silverman et al, 1998), particularly the frequent monitoring, immediate feedback, and quantitative and graphed goals. Participants in this study also indicated that they found these features to be some of the most helpful in promoting abstinence (reported in Raiff et al, 2013). …”
Section: Discussionmentioning
confidence: 63%
“…Cell phone and drug testing technologies allow for frequent assessment and reinforcement of alcohol and cigarette abstinence in the natural environment. These approaches are efficacious and acceptable to patients (Alessi & Petry 2013; Alessi & Rash 2017; Alessi et al, 2016; Kong 2013), as are Internet-based reinforcement procedures (Carpenter et al, 2015; Dallery & Glenn 2005; Dallery, Glenn, & Raiff 2007; Dallery, Raiff, & Grabinski 2013; Hertzberg et al, 2013; Meredith, Grabinski, & Dallery 2011; Raiff, Jarvis, Turturici, & Dallery 2013; Reynolds et al, 2015; Stoops et al, 2009). Coupling these technologies with mobile reinforcement procedures may support abstinence in real-time and lead to more effective and efficient delivery of CM, which may enhance and extend its benefits.…”
Section: Next Stepsmentioning
confidence: 99%
“…In one recent randomized clinical trial, Dallery et al (2013b) found that Internet-based CM promoted higher rates of abstinence (66.7 % negative COs) than a control group (25 % negative COs) during treatment. In addition to efficacy, Raiff et al (2013) evaluated the social validity of Internet-based CM and found high levels of acceptability among smokers, nonsmokers, and health-care professionals (for details about social validity assessment in clinical research, see Foster and Masch 1999). …”
Section: Technology-based Interventions To Promote Healthmentioning
confidence: 99%